Prognostic value of physiological tests for selection of promising elite rhythmic gymnasts - Zakharyeva, N. N.; Yashkina, E. N. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to find a set of physiological criteria to rate the variably skilled rhythmic gymnasts` functionality and potential competitive success in the top-ranking international competitions, with a special emphasis on different types of autonomous nervous regulation of heart, systolic/ diastolic blood pressure and respiration rates. Conclusion. The study found the functionality differences in the highly-skilled and elite gymnasts diagnosed with the vagotonic type of the autonomous nervous system control of HRV versus their sport qualifications and actual competitive success rates in the top-ranking international events. The top-ranking (ICSM) gymnasts were tested to be significantly different from the lower-skilled ones by mostly the ability to cope with the growing fatigue when solving intellectually challenging tasks and by the more sophisticated coordination abilities.